Study the Optical Properties of Polyvinyl Alcohol Thick Film Irradiated with Violet Laser (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:The aims study of this work is the effect of violet laser beam  irradiating on the optical properties of the Polyvinyl alcohol PVA before and after irradiation to a laser beam of different time 10, 20, 30 and 40 minute.Materials and Methods:The polymer powder PVA 0.008 mg  was dissolved in 7 ml distilled water at  temperature 40 °C and the thickness of the film was  3000 nm by using weight method to measure the thickness of the films. A semiconductor laser with a wavelength of 405 nm was used to irradiate the films.Results:The absorbance, transmittance and reflectance spectra of thick films before and after laser irradiation were plotted. The energy gap and optical constants were calculated.Conclusions:The irradiation with the violet laser causes a breakdown of the bonds, which causes a decrease in the absorbance and reflectance spectrum, while the energy gap increases.